2010
DOI: 10.1007/s10778-010-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Quasistatic and dynamic instability of one-support cylindrical shells under gyroscopic and nonconservative forces

Abstract: The paper deals with problem of critical states in single-support rods and cylindrical shells under axial follower forces and centrifugal inertial forces due to rotation. It is shown that depending on the relationship between these forces, loss of stability may be quasistatic or dynamic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…V.I. Gulyaev et al [8] studied critical states of cylindrical shells under the influence of longitudinal and centrifugal inertial forces as a result of rotation. It was shown that while these forces were interacting to each other, the dynamic loss or quasistatic loss of stability could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…V.I. Gulyaev et al [8] studied critical states of cylindrical shells under the influence of longitudinal and centrifugal inertial forces as a result of rotation. It was shown that while these forces were interacting to each other, the dynamic loss or quasistatic loss of stability could be observed.…”
Section: Introductionmentioning
confidence: 99%